Isolasi dan Uji Aktivitas Antimikroba Kapang Endofit dari Kayu Ulin (Eusideroxylon zwageri Teijsm & Binn.) (Isolation and Antimicrobial Activity of Endophytic Fungi from Ulin (Eusideroxylon zwageri Teijsm & Binn.)) - Nadra Khairiah; Rinne Nintasari (Kementerian Perindustrian, 2017)
Endophytic fungi are reported to be potential as antibacterial, antifungal, antioxidant, anticancer, and antivirus. One of the source of endophytic fungus is ulin (Eusideroxylon zwageri Teijsm & Binn.) which produced the same antimicrobial compound with ulin wood itself. The purpose of this research was to isolate endophytic caps from ulin wood branch, and tested the antimicrobial and antioxidant activity. The isolates were fermented on PDB media (Potato Dextrose Broth), and then tested the antimicrobial activity on Eschericiacoli, Pseudomonas aeruginosa, and Enterococcus aerogenes). In this research, there were two endofit isolates (white/PT and greenish black/HT). HT endophytic isolate exhibited strong antibacterial activity against the two pathogens (P. aeruginosa and E. coli) shown in 12 mm inhibition zone, while PT endophytic isolate exhibited the E. coli in 11.5 mm inhibition zone. The highest antioxidant activity found in HT endophytic shell was 47.47%. Keywords : antimicrobial, endophytic, Eusideroxylon zwageri, fungi, ulin